2011
DOI: 10.5322/jes.2011.20.9.1069
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Phosphate Flux at the Sediment-water Interface in Gamak Bay during the Hypoxic Water Mass

Abstract: The environmental changes related to hypoxic water mass were investigated at Gamak bay in summer times, June, July and August 2006. The hypoxic water mass was found, in first, at the northern area of Gamak bay on 27 June. This water mass has been sustained until the end of August and disappear on 13 September. In Gamak bay, the hypoxic water mass was closely related to geography. During the formation of oxygen deficiency, changes in dissolved nutrients was studied and found that on surface layer and lower laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
2
1
Order By: Relevance
“…This study found high concentrations of H 2 S, DIN, DIP, and DSi in the bottom water collected from GA4, consistent with previous studies [12,66]. The OEI was 16.5, indicative of severe eutrophication.…”
Section: Nutrient Elution and Diffusion Fluxes At The Bottom Seawater...supporting
confidence: 91%
See 2 more Smart Citations
“…This study found high concentrations of H 2 S, DIN, DIP, and DSi in the bottom water collected from GA4, consistent with previous studies [12,66]. The OEI was 16.5, indicative of severe eutrophication.…”
Section: Nutrient Elution and Diffusion Fluxes At The Bottom Seawater...supporting
confidence: 91%
“…Although the DIN elution flux (2.1 mmol/m 2 /d) in this study was lower than those in other dense fishery farms [32,[62][63][64], the DIP elution (1.5 mmol/m 2 /d) was considerably higher than those in the farms [32,[62][63][64]. This reflects that the labile-P contents in the surface sediments were significantly high in Gamak Bay relative to the adjacent bays [66].…”
Section: C N and P Mass Balances Under The Effects Of The Reducing En...contrasting
confidence: 73%
See 1 more Smart Citation
“…A large amount of phytoplankton is produced under the thermocline in summer due to an abundance of nutrients and sufficient solar radiation, both of which are required for photosynthesis. Although this study did not provide information on CTD and nutrient profiles according to water depth, Kim et al (2006) and Kim et al (2011) observed that the thermocline was mainly formed at depths of 3-5 m and 2-5 m. In turn, the organic matter that sinks to the bottom is decomposed and oxygen consumption rates increase. Additionally, the oxygen consumption rate of sediments increases, which further exacerbates hypoxia (Kim et al, 2006).…”
Section: Study Areamentioning
confidence: 72%